The effect of muscle actions on the level of connective tissue damage - de C. Nogueira, A.; Vale, R. G. S.; Gomes, A. L. M.; Dantas, E. H. M. (Research in Sports Medicine, 2011)
The aim of this study was to compare the effect of concentric with eccentric muscle actions on the resulting level of damage to connective tissues by urinary concentration of hydroxyproline. Twenty-one male volunteers were divided into control group (CG), experimental concentric group (ECG), and experimental eccentric group (EEG). The measures of hydroxyproline were performed at three times: pretest, fourth week, and posttest. Biceps curl and chest press exercises also were performed with three sets of 10 repetitions two times per week for both experimental groups. Analysis of variance (ANOVA) showed a significant difference between pretest of the CG and pretest of the ECG (p = 0.002), and between pretest and posttest for the EEG (p = 0.029). Therefore, this study concluded that the level of damage to the connective tissue is greater when exercises involving eccentric muscle actions are performed. The continuity of training, however might reduce this damage.